Bio‐based nanoemulsion formulation, characterization and antibacterial activity against food‐borne pathogens. (7th September 2012) - Sugumar, Saranya; Nirmala, Joyce; Ghosh, Vijayalakshmi; Anjali, Haridasan; Mukherjee, Amitava; Chandrasekaran, Natarajan
Abstract The current study deals with the formulation and characterization of bio‐based oil in water nanoemulsion and its potential antibacterial activity. A typical v/v% of eucalyptus oil (16.66%), Tween 80 (16.66%), and water (68.68%) was prepared by ultrasonication method. The mean droplet size was 17.1 nm as confirmed by dynamic light scattering. Different concentrations of the formulation ranging from undiluted to 10‐, 100‐, and 1000‐fold dilutions were used to check the antibacterial activity in three different microorganisms, namely, Bacillus cereus, Staphylococcus aureus (Gram‐positive), and Escherichia coli (Gram‐negative). All three species showed a 100% bactericidal at the 10‐fold dilution of the nanoemulsion formulation in the following order: B. cereus at 0th min, S. aureus at 15 min and E. coli at 1 h, respectively. A 10‐fold dilution of the nanoemulsion showed that, the cytoplasmic content leakage from the bacterial species was high for S. aureus when compared to B. cereus and E. coli as determined by UV–Vis spectroscopic method. Fluorescence microscopic technique further confirmed this study.